Aircraft observations on a continuous haze pollution event in Shijiazhuang area - Zhou, Xuesi; Sun, Xiaoshen; Yang, Yang; Zhang, Xiaorui; Huang, Zhaochu; Cui, Yi; Huang, Yi (Frontiers in Earth Science, 2023)
A continuous haze event was recorded on November 14th~17th, 2020 over Shijiazhuang. Two flights of King-air 350 meteorological research aircraft were performed on November 14th and 16th for the retrieval and observations of meteorological elements, aerosols, and black carbon. In this study, we combined airborne data with air pollution data (PM2.5), ground meteorological data, and ERA-5 reanalysis data to describe the vertical distribution of aerosols (namely 0.1~3.0μm) and black carbon. We further explicated the formation of this haze event. PM2.5 pollution dominated this haze event, and the highest concentration of PM2.5 was 209μg/m3. The intensity and height of thermal layers highly linked with the vertical transport of pollution. The highest number concentration of aerosols and black carbon was found below the thermal layers on both airborne sounding days. On the 14th, both BC and aerosol concentrations showed unimodal distribution, and the highest concentrations of BC and aerosols were 12683ng/m3 and 6965.125#/L at 250m within layer Ⅰ. The intensity of the thermal layer near-ground was weaker on the 16th that the number concentrations of BC and aerosols also remained at high levels in layer Ⅱ. Backward trajectories of air mass indicated the long-range transport of pollution contributed to the high level of pollution on the 16th. Vapor conditions were more favorable for aerosols growth through moisture absorption. The maximum concentration of 943.58#/L was recorded at particles with a diameter of 0.4μm on the 16th, while 749.26#/L was reached at 0.14μm on the 14th. The corresponding height was consistent with the height of maximum concentration in the vertical distribution.